Influence of Exopolymeric Materials on Bacterially Induced Mineralization of Carbonates - Bains, A.; Dhami, N.; Mukherjee, Abhijit; Reddy, M. (Humana Press Inc., 2015)
Microbially induced calcium carbonate precipitation is an immensely growing technology for restoration and remediation of building materials. The investigation on role of exopolymeric substances and biofilms in microbially induced calcium carbonate precipitation suggested that these exopolymeric materials play major role in carbonate precipitation in Bacillus megaterium SS3 along with enzymes urease and carbonic anhydrase. The concentration of EPS directly affects the precipitation of carbonate precipitates which might be due to capturing of Ca2+ ions by acting as nucleation site. Components of the media and presence of calcium also play crucial role in production of exopolymeric substances along with affecting the morphology of carbonate precipitates.